A taxonomic revision of Garcinia section Garcinia (Clusiaceae) in Thailand - Chatchai Ngernsaengsaruay; Pichet Chanton; Nisa Leksungnoen; Minta Chaiprasongsuk; Raweewan Thunthawanich (PhytoKeys, 2024)
Garcinia section Garcinia (Clusiaceae) is revised for Thailand with three species and one variety, i.e., two native species: G. celebica and G. exigua, and one cultivated species: G. mangostana var. mangostana. Detailed morphological descriptions, illustrations, and an identification key to the species are presented, along with notes on distributions, habitats and ecology, phenology, conservation assessments, etymology, vernacular names, uses, and specimens examined. The section is recognized by its terminal inflorescences of simple cymes, or sometimes a solitary flower; flowers with 4 sepals and 4 petals; male flowers often with a pistillode, and stamens united into a single 4-lobed or 4-angled bundle, and with 2-thecous anthers; usually multilocular ovaries and stigmas with distinct or weak lobes and smooth or rough; and fruits with a smooth surface. Three associated synonyms of G. celebica: G. ferrea, G. basacensis, and G. hombroniana, are lectotypified here in a second-step. In Thailand, Garcinia celebica is found in a very wide variety of habitats, at elevations of 0–1,500 m amsl., and is known to be naturally distributed in all floristic regions. G. exigua is found in dry evergreen forest on limestone hills and in littoral dry evergreen forest on limestone hills, at elevations of 50–100 m amsl. in Krabi Province, the peninsular region. G. mangostana var. mangostana is found only in cultivation. Garcinia exigua has a conservation status of Vulnerable [VU B2ab(iii)] and the other two species have a conservation status of Least Concern [LC]. The fleshy pulp surrounding the seeds of two species, G. celebica and G. mangostana var. mangostana is edible and has a sweet-sour taste.